Peran Guru Dalam Memotivasi Belajar Siswa Kelas IV Di SDN 1 Wergu Wetan - Oktaviana Dwi Rahmadhani; Nihayatur Rohmah; Syibilla Oktavia Malaka Sari; Rani Setiawaty (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research aims to explain the role of teachers in motivating learning of class IV students at SDN 1 Wergu Wetan. The instruments of this research are observation guidelines, interview guidelines and documentation tools in the form of cellphones and cameras. The method used in this research is qualitative using a qualitative descriptive type, the research subject is a class IV teacher at SDN 1 Wergu Wetan. Data collection techniques in this research used observation, interview and documentation techniques. The data sources in this research, the author collected various reference sources which are the subject of discussion, come from books, journal articles, proceedings, and so on. The results of this research show that the role of teachers is very important in increasing students' learning motivation. To motivate students, teachers have several ways, such as giving appreciation to students, managing the class well, delivering material using teaching aids, and learning objectives can be achieved.